Comparison of Selected National Healthcare Systems' Efficiency - Biernacki, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The efficiency of selected national healthcare systems in the European Union was analyzed with Eurostat from 2004 to 2013 data, in particular considering countries which made a transition after 1990. The analysis of efficiency was performed using DEA – a nonparametric method implemented in MaxDEA 6.3.mdb software. Estonia, Hungary and Slovakia improved their efficiency of medical treatment, Poland and the Czech Republic deteriorated, while effectiveness of medical treatment measured by HLY improved in the Czech Republic and deteriorated in Poland in the period under study. Among the transition economies after 1990, Poland’s healthcare system was most efficient as a result of healthy population and relatively low financial inputs to healthcare. It is worth emphasizing that when life expectancy is above the trend line, then people in those countries live longer, whereas if infant mortality is below the trend line, it shows that obstetrical care in those countries is excellent
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 7-16
Keywords: health care system; efficiency; DEA